Media Massa dalam Situasi Konflik: dari Bandwagon Effect Sampai Peace Narrative - Aloysius Ranggabumi Nuswantoro (Jurnal Aspikom)
Conflict occurs between two or more parties with different interests. Media related to conflict. The ability of the media to influence public opinion is the biggest element in the relationship between media with conflict. The media in this context can be a party that sparked the conflict but could also act as resolutor conflict. Media as a provocateur when play became an arm of one of the conflicting parties, while a conciliator conflict when showing neutrality and information that tends to peace (peace narrative). And theoretical studies should be conducted searches empirical facts on this subject, to clarify the position, the position and role of media in conflict situations. The results can also be used to see the extent to which the media contribute to creating conditions of public space and democratic deliberative. Against this, the choice to stick with journalism be the most appropriate choice for the media in an effort to maintain its position as an agent of democracy in society.